A Bi-Level Programming-Based Method for Service Composition Optimization of Collaborative Manufacturing of Sewing Machine Cases - Gan Shi; Shanhui Liu; Keqiang Shi; Langze Zhu; Zhenjie Gao; Jiayue Zhang (Machines)
Aiming at the problem of optimizing the composition of manufacturing resources in part-level outsourcing of sewing machine case manufacturing, this paper proposes a service composition optimization method based on bi-level programming. We analyze the structure and production process of sewing machine cases, determine the required service composition of manufacturing resources, and establish the evaluation indicator system of manufacturing service composition in line with the interests of multiple parties. We also introduce the idea of bi-level programming, construct the optimization model of manufacturing service composition of sewing machine cases based on bi-level planning, analyze the characteristics of NSGA-Ⅱ (Non-dominated Sorting Genetic Algorithm II) algorithm and the improvement strategy, and complete the solution of the optimization model of manufacturing service composition of sewing machine cases. The experimental results show that the composition optimization method and the algorithm improvement strategy can well solve the bi-level programming model of sewing machine cases in the case of complex feature information and avoid falling into the local optimal solution.